Warming increases soil carbon input in a Sibiraea angustata-dominated alpine shrub ecosystem. (27th August 2021) - Liu, Mei; Wen, Jia-Hao; Chen, Ya-Mei; Xu, Wen-Juan; Wang, Qiong; Ma, Zhi-Liang
Abstract: Plant-derived carbon (C) inputs via foliar litter, root litter and root exudates are key drivers of soil organic C stocks. However, the responses of these three input pathways to climate warming have rarely been studied in alpine shrublands. By employing a 3-year warming experiment (increased by 1.3 °C), we investigated the effects of warming on the relative C contributions from foliar litter, root litter and root exudates from Sibiraea angustata, a dominant shrub species in an alpine shrubland on the eastern Qinghai-Tibetan Plateau. The soil organic C inputs from foliar litter, root litter and root exudates were 77.45, 90.58 and 26.94 g C m −2, respectively. Warming only slightly increased the soil organic C inputs from foliar litter and root litter by 8.04 and 11.13 g C m −2, but significantly increased the root exudate C input by 15.40 g C m −2 . Warming significantly increased the relative C contributions of root exudates to total C inputs by 4.6% but slightly decreased those of foliar litter and root litter by 2.5% and 2.1%, respectively. Our results highlight that climate warming may stimulate plant-derived C inputs into soils mainly through root exudates rather than litter in alpine shrublands on the Qinghai-Tibetan Plateau. Graphical Abstract: